Oxford urdu ka guldasta Champa grade 6 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Champa (Grade 6)" is a collection of engaging Urdu stories, poems, and rhymes designed for sixth-grade students. The book helps enhance students' Urdu language skills, focusing on vocabulary, comprehension, and writing. It presents a variety of interesting narratives and poems that introduce moral lessons, cultural themes, and valuable life skills. With colorful illustrations and thoughtfully crafted content, the book encourages students to develop a deeper understanding of the Urdu language while making the learning experience enjoyable and educational.
Keywords: Urdu : Textbook